The Effect of Financial Ratios on Stock Return of Telecommunication Companies Listed on IDX 2009 – 2016. - Geni, Puti Lenggo; Alfarisi, Mohamad Fany (Business and Investment Review, 2023)
This study aims to analyze the influence of Return On Equity (ROE), Earning Per Share (EPS), Debt Equity Ratio (DER) separately and simultaneously on stock returns of Telecommunication Companies. This research was analyzed by quantitative analysis. The method used to analyze the data was panel data method using eviews 9 as a data processing tool. Of the three independent variables examined in this study, based on the t test (partially) the Return On Equity, Earning per Share and Debt to Equity Ratio have no significant effect on stock returns of telecommunications companies listed on the IDX in 2009 - 2016. Simultaneously ( test F) the five independent variables studied together did not have a significant effect on the stock returns of telecommunications companies listed on the IDX from 2009-2016. The independent variables studied were only able to explain the stock return variability of 1.2%.     Abstrak   Penelitian ini bertujuan untuk mengetahui Menganalisis Pengaruh Pengaruh Return On Equity (ROE), Earning Per Share (EPS), Debt Equity Ratio (DER) secara sendiri-sendiri dan simultan terhadap return saham Perusahaan Telekomunikasi. Penelitian ini dianalisis dengan analisa kuantitatif metode yang digunakan untuk menganalisis data adalah metode data panel dengan menggunakan eviews 9 sebagai tools pengolahan data. Dari tiga variabel bebas yang diteliti dalam penelitian ini, berdasarkan uji t (secara parsial) maka Return On Equity, Earning per Share dan Debt to Equity Ratio tidak berpengaruh signifikan terhadap return saham perusahaan telekomunikasi yang terdaftar di BEI tahun 2009 – 2016. Secara simultan (uji F) kelima variabel bebas yang diteliti bersama-sama tidak memberikan pengaruh signifikan terhadap return saham perusahaan telekomunikasi yang terdaftar di BEI dari tahun 2009-2016. Variabel-variabel bebas yang diteliti hanya mampu menjelaskan variabilitas return saham sebesar 1,2%.